Three new species of Galumnidae (Acari: Oribatida) from Cat Tien National Park, southern Vietnam - Ermilov, Sergey G.; Anichkin, Alexander E. (Zootaxa, 2010)
Three new species of oribatid mites of the family Galumnidae, Galumna acutirostrum sp. nov., Galumna levisensilla sp. nov., Neogalumna seniczaki sp. nov., are proposed and described. All three are from sandy soil in a dipterocarp forest of Cat Tien National Park (southern Vietnam). Diagnostic keys to the Vietnamese species of Galumna (Galumna) and known species of Neogalumna are presented.